2017
DOI: 10.1007/s11082-017-1129-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient heat extraction by double diamond heat-spreaders applied to a vertical external cavity surface-emitting laser

Abstract: We compare the heat extraction efficiency for a standard Vertical External Cavity Surface-Emitting Laser and the distributed Bragg reflector (DBR)-free structure employing a single and double diamond heat-spreaders, respectively. Both heterostructures grown by Molecular Beam Epitaxy employ two identical active regions designed for emission at 980 nm. We show that the thermal resistance has been decreased 15 times when there is no DBR and heat is extracted from both side of active region. For DBR-free laser no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For lasing wavelengths near 1 µm, the single heatspreader geometry has demonstrated an output power of 6 W when directly bonded to diamond [8]. Recently, using a single SiC heatspreader, Mirkhanov et al [9] reported 6 W of output power at a coolant temperature of 12°C, and 10.1 W at −10°C, while dual‐diamond‐heatspreader DBR‐free SDLs have yielded 3.5 W, thus far limited solely by the available pump power [10]. In this paper, we directly compare the laser performance of DBR‐free SDLs using these two geometries.…”
Section: Introductionmentioning
confidence: 99%
“…For lasing wavelengths near 1 µm, the single heatspreader geometry has demonstrated an output power of 6 W when directly bonded to diamond [8]. Recently, using a single SiC heatspreader, Mirkhanov et al [9] reported 6 W of output power at a coolant temperature of 12°C, and 10.1 W at −10°C, while dual‐diamond‐heatspreader DBR‐free SDLs have yielded 3.5 W, thus far limited solely by the available pump power [10]. In this paper, we directly compare the laser performance of DBR‐free SDLs using these two geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxial structure is bonded to a single or in-between two transparent heat sinks. Single crystal diamonds are most frequently used as heat sinks due to their high thermal conductivity [27]]. The more cost-effective SiC is also widely used, since single samples of large, good optical quality crystal are available [28,29].…”
Section: Heterostructure Design and Growthmentioning
confidence: 99%
“…Recent optical systems, e.g. light-emitting diodes (LEDs, [11,30,72]) or verticalexternal-cavity surface-emitting-lasers [8,20], feature multilayer thin films, which transmit or reflect designated parts of the wave spectrum to achieve a certain functionality [34,39]. For example, multi-layer thin films are widely used for antireflection coating [1,14,49,59,60].…”
Section: Introductionmentioning
confidence: 99%